IMPROVING PERFORMANCE OF GRADE 12 STUDENTS IN SOLVING PROBLEMS IN DIRECT CURRENT CIRCUIT THROUGH 4MAT TEACHING MODEL - Tumanguil, Maria Loresa (International Journal of Arts, Sciences and Education, 2021)
This study aimed to look into the effectiveness of 4MAT Teaching Model in solving problems on direct current circuits of Grade 12 students. Using True-Experimental Research Design, there were two groups having 38 students respectively. The said groups were given a pre-test about solving problems on direct current circuits. One group which was the Experimental, was exposed to the 4MAT Teaching Model technique while the other group which was the Control, was exposed with the traditional way of teaching particularly the lecture method. The administration of post-test happened after six (6) class sessions. Using Paired Sample T-test via SPSS, the results showed a computed probability of 0.000. This implies that there is a significant difference between the post test score results of the control versus experimental group. The mean of 13.82 for experimental group indicated that the section have higher performance in the competency of solving problems involving direct current circuits using the 4MAT Teaching Model compared to the controlled group with a mean score of 11.45, wherein lecture method was administered as its mode of teaching. Using the Cohen’s d analysis for t-test, the computed value is 1.3989 which means that 4MAT Teaching Model has a large effect on the performance of students in solving direct current circuits. This also indicates that approximately 92% of the students scored higher in experimental group than those who were on the control set.